Impact of human land-use and rainfall variability in tropical dry forests of southwest Madagascar during the late Holocene - Razanatsoa, Estelle (Department of Biological Sciences, 2019)
Over the last 2000 years, climatic and anthropogenic factors have influenced vegetation in Madagascar, but the contribution of these two factors has been the subject of intense debate, a debate hampered by the scarcity of palaeoecological studies on the island. Southwest Madagascar is semi-arid and comprises fragmented tropical dry forests where human subsistence strategies are diverse. Therefore, it provides a perfect setting to generate new palaeoecological records and investigate vegetation response to changes in human land-use and rainfall variability. The aim of this thesis is to understand how and when land-use changed, and rainfall variability impacted the landscape in the southwest region, using dendroclimatological and palaeoecological approaches. Carbon isotopes in the rings of four baobab trees (Adansonia spp.), were compared with pre-existing palaeoclimate data to produce rainfall records for the past 1700 years. Pollen, carbon isotopes, and charcoal in sediment cores from two lakes namely Lake Longiza and Lake Tsizavatsy (located in the northern and southern sites respectively in southwest Madagascar) were analysed to produce vegetation and fire records during the late Holocene in the region. Combination of the four baobab isotope records yields a new 700-year record for the southwest, which suggests an aridity trend over time, associated with a long-term reduction and increase in the duration of wet and dry periods respectively. Drying was more pronounced for the southern site than the northern site. A comparison with a high-resolution record from the northwest region allowed the rainfall of the southwest to be extended back to the last 1700 years as follows: from AD 300-500, the southwest region experienced a dry period which was followed by a wet period until AD 1000. Subsequently, there was a dry period from AD 1000-1250, followed by a wet period in the southwest. The period from AD 1300-1400 represented the wettest period in the record, followed by a decreasing wet period until AD 1600. The period between AD 1600 and 1800 represented the driest period, peaking around AD 1700. This was followed by a relatively wet period of about 50 years and another 100-year dry period. The last period assessed, from AD 1985 to 2000, was a relatively wet period. Such variability of the rainfall might have affected ecosystems and human land-use in the region. The tropical dry forest biome of southwest Madagascar has taxa from the dry forest, riparian forest and savanna woodland in the pollen records of both sites. In the core from the northern site (Lake Longiza), the pollen record suggests a heterogeneous mosaic of dry forest and riparian forest that was present over the last 2400 years. In the earliest part of the record, the community was dominated by trees from both the dry forest and riparian ecosystems. The onset of changes was recorded around AD 420, with a decrease in dry forest and riparian trees and an increase in grasses and xerophytics, possibly driven by dry conditions. This was followed by a short recovery of trees and C3 plants around AD 870 punctuated by a decrease in dry forest taxa around AD 980, possibly associated with the suggested expansion of pastoralism. After this period, the landscape became more open and grassier, as indicated by the dominance of C4 plants in the stable isotope record. Similar patterns of change in the pollen record, with a further increase in grasses and pioneer taxa, were recorded around AD 1900. Charcoal influx also started to increase drastically at this time, suggesting fire and forest clearance associated with a shift to agriculture. These large shifts in human land-use (probably a combination of both pastoralism and agriculture) coincided with the decline of floral diversity of the landscape, as indicated by pollen rarefaction. However, the diversity of the floral community gradually recovered, because of the persistent heterogeneity of the landscape. The core from the southern site (Lake Tsizavatsy) had a basal date of approximately 700 years BP but presented a hiatus of about 500 years from AD 1420-1910. The preceding period of AD 1300-1420 was marked by a decrease in the abundance of trees during the wettest period in the region, which was most likely because of human activities (foraging and pastoralism), as inferred by the increase in charcoal influx and pioneer taxa. During the second period, from AD 1910- 2010, there was an increase in xerophytic taxa, which suggests a long dry climate, recorded prior to this period. In addition, from AD 1950, trees decreased while pioneer taxa increased, despite the stable influx of charcoal recorded during this period. This possibly indicates the effect of human activities that did not involve the use of fire, probably conducted by ethnicities other than the forager communities, which are still present in the area today. This thesis contributes significantly to the understanding of palaeoclimate, palaeoecology and the history of human subsistence in a biodiverse region of Madagascar, where no other record is currently available. Results from stable isotope analysis from baobabs showed a drying trend over the past 700 years, which has interacted with land-use to affect vegetation structure and composition over time. The pollen and charcoal results suggest the northern site, where vegetation was a mosaic of dry forest and riparian forest, experienced an impact of human activities through a shift to agriculture especially in the last 100 years. The savanna woodland of the southern site, however, was less affected by humans, probably as occupants were subsistence foragers, but the vegetation had a higher response to aridity. The results show that two distinctive human subsistence (pastoralism and foraging) were present simultaneously in the region until modern times. The northern site has evolved possibly from foraging into extensive agriculture, probably related to the fertility of the alluvial soil in the area, while the southern community remained dominated by foragers, while adopting today a seasonal practice of agriculture. From a conservation perspective, strategies of conservation for each ecosystem investigated here are proposed. In the northern site, monitoring and reducing fire-use within the dry forest ecosystem would allow tree recovery. In addition, restoring and establishing protected areas within the riparian forest would allow these ecosystems to act as refugia for regional biodiversity. Such measures will likely reduce the pressure on these ecosystems, where agriculture is a threat due to the availability of both water and fertile soil in their surroundings. Alternative livelihoods are required for the northern populace, for example through the exploitation of invasive aquatic plants such as Typha, which can be used in making of handcrafted artefacts, to reduce pressure on forest ecosystems through agricultural practices. For the southern site, maintaining the resilience of the savanna woodland through reforestation of functional species is also important to allow sustainability of services provided by these ecosystems. These strategies are applicable locally for Madagascar and for worldwide tropical dry forests, one of the globally most threatened vegetation types due to anthropogenic pressure and climate change.